Semi-continuous cultivation of microalgal consortium using low CO 2 concentration for large-scale biofuel production - Sunisa Boonma (2019)
© 2019 Journal of Biotech Research. In this study, the microalgal consortium (MC) was cultivated with low CO 2 concentration (1% v/v) in the semi-continuous outdoor open system in order to apply for large-scale biofuel production. The results found that the recorded levels of dry weight, lipid content of MC cultured with 1% CO 2 supplementation in all cycle were higher than of those with ambient air (0.03% CO 2 ) supplementation. The means of biomass concentration and lipid content of the MC with 1% CO 2 supplementation were 0.41+0.04 g/l and 17.3+0.77% of dry weight, respectively. CO 2 supplementation also had strongly affected on biovolume ratio of microalgae. The results of characteristics and chemical compositions analysis found that cultivating algae with a low concentration of CO 2 supplement (1% v/v) enhanced the properties that make MCB suitable as a raw material for biofuel production. MCB cultivated with CO 2 supplement showed high volatile matter content, carbon content, and HHV (78.01 wt%, 45.68 wt%, and 16.37 MJ/Kg, respectively). The major fatty acids from MCB under 1% CO 2 concentration were palmitic acid and oleic acid. Therefore, cultivating microalgae with low CO 2 concentration was considered suitable for applications in large scale biofuel production.